Unexpected Thrombocytopenia and Anemia in Cynomolgus Monkeys Induced by a Therapeutic Human Monoclonal Antibody. (October 2013) - Everds, Nancy; Li, Nianyu; Bailey, Keith; Fort, Madeline; Stevenson, Riki; Jawando, Remi; Salyers, Kevin; Jawa, Vibha; Narayanan, Padma; Stevens, Erin; He, Ching; Nguyen, Mai Phuong; et al.
Cynomolgus monkeys dosed with a therapeutic monoclonal antibody (mAbY.1) at ≥50 mg/kg had unexpected acute thrombocytopenia (nadir ∼3, 000 platelets/µl), sometimes with decreases in red cell mass. Increased activated macrophages, mitotic figures, and erythrophagocytosis were observed in the spleen. Binding of mAbY.1 to cynomolgus peripheral blood cells could not be detected in vitro . mAbY.1 induced phagocytosis of platelets by peripheral blood monocytes from cynomolgus monkeys, but not from humans. mAbs sharing the same constant domain (Fc) sequences, but differing from mAbY.1 in their variable domains, bound competitively to and had similar biological activity against the intended target. None of these antibodies had hematologic liabilities in vitro or in vivo . Neither the F(ab')2 portion of mAbY.1 nor the F(ab')2 portion on an aglycosylated Fc (IgG1) framework caused phagocytosis of platelets in vitro . These data suggest that the hematologic effects of mAbY.1 in cynomolgus monkeys likely occurred through an off-target mechanism, shown to be driven by 1 to 3 amino acid differences in the light chain. The hematologic effects made mAbY.1 an unsuitable candidate for further development as a therapeutic agent. This example demonstrates that nonclinical safety studies may be essential for understanding off-target effects of mAbs prior to clinical trials.